Global, regional, and national burden of childhood cardiovascular disease: trends from 1990 to 2021 - Wang, Mingling; Yi, Junling; Chen, Zuolei (Frontiers in Pediatrics, 2024)
BackgroundChildhood cardiovascular disease (CVD) is an emerging public health concern, with rising incidence linked to obesity and diabetes. Despite advancements in care, significant disparities persist across regions and socioeconomic groups. This study analyzed the global, regional, and national burden of childhood CVD from 1990 to 2021.MethodsA cross-sectional study utilizing data from the Global Burden of Disease (GBD) 2021 was conducted. We analyzed children aged 0–14 years, categorizing them into age groups and assessing trends in incidence, mortality, and disability-adjusted life years (DALYs) across 204 countries. Statistical analyses included linear regression to calculate estimated annual percentage changes and assess temporal trends.ResultsThe study revealed a 25% global increase in childhood CVD incidence over three decades, with significant disparities observed across different socioeconomic regions. Mortality and DALYs associated with CVD had decreased globally by 59% and 55% respectively, reflecting advances in medical technology and healthcare access. However, these improvements were not uniformly distributed, with low socio-demographic index regions exhibiting both the highest incidences and slowest declines in CVD-related health burdens. Environmental risks, such as extreme temperatures, also contributed to CVD mortality.ConclusionsWhile mortality and DALYs due to childhood CVD have declined globally, rising incidence and persistent disparities highlight the need for targeted interventions. Addressing socio-economic factors and enhancing access to quality care are crucial for reducing the global burden of childhood CVD.